(3GdaQhSjI hGdefGUH GdMQHjIs - (3fLe GdOjf MSf GdCMOH GdQeGMs
(3ChdgG (B:s
(3GdMeO ddg GdPi GYR Cgd WGYJg , CcQege HGdEjeGf hTQage HGdbQBf hChge HGdLgGO s
(3BNQgG (B:s
(3Je GdeLehY GdeHGQc HMeO Gddg hYhfg s
(3CNP eGOJg Yf CHjg hGLOGOg hef UMHge hdge YdGbI HgP g GdUfGYIs
(3HChd GdfSNI OQGSI Hbde GdCSJGP EHQGgje GdWMGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B26 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs